2017
DOI: 10.1002/bdm.2070
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Scales Do Not Reliably Predict Maximizing Behavior in Decisions from Experience

Abstract: In this paper, we explore the relationships between psychometric and behavioral measures of maximization in decisions from experience (DfE). In two experiments, we measured choice behavior in two experimental paradigms of DfE and self‐reported maximizing tendencies using three prominent scales of maximization. In the repeated consequentialist choice paradigm, participants made repeated choices between two unlabeled options and received consequential feedback on each trial. In the sampling paradigm, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We hypothesize a preference for an option with a higher EV over an option with a lower EV, regardless of the degree of maximizing. Harman, Weinhardt and Gonzalez (2018) provided initial evidence for our hypothesis. They found that participants were more likely to choose options with high EVs (and thus high expectations) than options with low EVs (and thus low expectations).…”
Section: The Best Optionmentioning
confidence: 55%
“…We hypothesize a preference for an option with a higher EV over an option with a lower EV, regardless of the degree of maximizing. Harman, Weinhardt and Gonzalez (2018) provided initial evidence for our hypothesis. They found that participants were more likely to choose options with high EVs (and thus high expectations) than options with low EVs (and thus low expectations).…”
Section: The Best Optionmentioning
confidence: 55%
“…Although measures of general maximizing are useful, it is unlikely (and arguably impossible) that people maximize for all the decisions they make. This could explain why some researchers have found that measures of general maximizing do not always predict maximizing behavior (e.g., Harman, Weinhardt, & Gonzalez, 2018). Although people have general maximizing tendencies, maximizing behavior may manifest itself only for certain decisions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%